Current Concepts of Corticosteroids Use for the Prevention of Bronchopulmonary Dysplasia - Perrone, Serafina; Orlando, Serena; Petrolini, Chiara; Marinelli, Francesca; Moretti, Sabrina; Corradi, Mara; Giordano, Maurizio; De Bernardo, Giuseppe (Current Pediatric Reviews, 2023)
Despite using antenatal steroids, surfactants and protective ventilation, bronchopulmonary dysplasia (BPD) affects 10-89% of preterm infants. Since lung inflammation is central to the BPD pathogenesis, postnatal systemic corticosteroids could reduce the risk of BPD onset in preterm infants, but short and long-term adverse consequences have been underlined in literature after their use (i.e., hyperglycaemia, hypertension, hypertrophic cardiomyopathy, growth failure, gastrointestinal bleeding, cerebral palsy). Alternative therapeutic strategies such as postponing corticosteroid administration, lowering the cumulative dose, giving pulse rather than continuous doses, or individualizing the dose according to the respiratory condition of the infant have been proposed to avoid their adverse effects. Dexamethasone remains the first-line drug for newborns with severe pulmonary disease beyond the second to the third week of life. Hydrocortisone administration in very preterm infants does not appear to be associated with neurotoxic effects, even if its efficacy in preventing and treating BPD has yet been clearly demonstrated. Alternative methods of corticosteroid administration seem promising. A positive effect on BPD prevention occurs when budesonide is nebulized and intratracheally instilled with a surfactant, but more data are required to establish safety and efficacy in preterm newborns. Additional studies are still needed before the chronic lung disease issue, and its related challenges can be solved.
Keywords: oxygen